Description of Student Academic Anxiety Level III Sidoarjo D3 Nursing Program Health Polytechnic Ministry of Health Surabaya - Suryadianto, Sabrina Aulia; Sulystiono, Dony; Maziyah, Alfi (Global Ten Public Health and Nursing Journal, 2024)
WHO research results in 2019 show that depression and anxiety cause loss global economy of 1 trillion USD each the year consequence loss productivity resource human. Worry is feeling No easy, worried, all at once scared the research design used in research This is research "descriptive"  design purposeful research  For describe current events. According to  (Cassady et al., 2019) Worry academic is room scope covering area worry related with activity academic. Study Descriptive aim For make description in a manner systematic, factual and accurate about facts, properties population area certain. Based on results study level worry student level 3 D3 Nursing Sidoarjo part big respondent experience level worry currently that is amounted to 74 students (78.7%). obtained that aspect worry academic half from respondents (50%) experienced aspect worry academic Because expectation self that is a total of 47 students level 3. Research results on show reason anxiety in students the different between One individual with others. As for the results This strengthened with question open related perceived anxiety moment this, mostly that causes student experience worry moment This is how difficult share time For do task end (KTI).